INFLUENCE OF BIOTIC AND ABIOTIC FACTORS ON THE OCCURRENCE AND ABUNDANCE OF MACROBRACHIUM DAYANUM - CHAKRABARTI, SAUMEN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
Occurrence of prawn species Macrobrachium dayanum was studied in freshwater wet land ecosystem of Tripura (latitude 23'50'15" N and longitude 91'15'45" E) during 2000 to 2002. Notable biotic and abiotic features of the wetland were also observed and their degree of influence over the seasonal abundance of the said prawn was noted. The result was evaluated through correlation coefficient and multiple regression analysis. ANOVA depicted the significant nature of regression (F=99.99. p < 0.01).